Integrated bioethanol production to boost low-concentrated cellulosic ethanol without sacrificing ethanol yield. (February 2018) - Xu, Youjie; Zhang, Meng; Roozeboom, Kraig; Wang, Donghai
Highlights: High ethanol titers and ethanol yield can be achieved via integrated designs. Co-fermentation of starch and biomass can boost ethanol titers and yields. High ethanol concentration (130.2 g/L) can lower distillation cost. The co-fermentation technology could be applied to various pretreated biomass. Abstract: Four integrated designs were proposed to boost cellulosic ethanol titer and yield. Results indicated co-fermentation of corn flour with hydrolysate liquor from saccharified corn stover was the best integration scheme and able to boost ethanol titers from 19.9 to 123.2 g/L with biomass loading of 8% and from 36.8 to 130.2 g/L with biomass loadings of 16%, respectively, while meeting the minimal ethanol distillation requirement of 40 g/L and achieving high ethanol yields of above 90%. These results indicated integration of first and second generation ethanol production could significantly accelerate the commercialization of cellulosic biofuel production. Co-fermentation of starchy substrate with hydrolysate liquor from saccharified biomass is able to significantly enhance ethanol concentration to reduce energy cost for distillation without sacrificing ethanol yields. This novel method could be extended to any pretreatment of biomass from low to high pH pretreatment as demonstrated in this study.